Nutritional quality of foods according to the Nova food classification system after a behavioral economics intervention in food pantries - Rossi, Kristen; Gombi Vaca, Maria F.; Schwartz, Marlene B.; Caspi, Caitlin (Frontiers in Public Health, 2025)
IntroductionConsumption of ultra-processed foods has been linked with poor health outcomes. Using the Nova food classification system to measure the level of food processing, this study assessed whether foods selected by food pantry clients were more favorable following a behavioral economics food pantry intervention.MethodsThe study analyzed secondary data from a group-randomized evaluation in 11 Minnesota food pantries. Food items selected by 187 clients (85 intervention, 102 control) were categorized according to Nova in one of four categories: (1) unprocessed/minimally processed, (2) culinary ingredients, (3) processed foods, or (4) ultra-processed foods. In each client cart, the energy share (% of total calories) of each Nova food category was calculated. Adjusted mixed linear models were used to test the post-intervention differences in the energy share of Nova food categories between intervention conditions.ResultsOn average, unprocessed/minimally processed foods represented 34.6% of the energy share among carts in the intervention group and 33.8% among client carts in the control group. Ultra-processed foods represented 43.5 and 41.1% of the foods in the control and intervention groups, respectively. In the adjusted models, no statistically significant differences in the energy share of Nova categories were found between foods selected by clients in the pantries in the two conditions.DiscussionNeither a reduction in client selection of ultra-processed foods nor an increase in unprocessed/minimally processed foods were among the benefits of the intervention. Future research should explore interventions targeting Nova food categories and subgroups to improve the nutritional quality of foods in food pantries.